Nurturing Faith at the Margins: Mental-Spiritual Education for Muslim Children in Bogor through Tilawati and Tahfidz - Alfi Syahriyani; Nurul Irfan; Nawawi; Amelia Zakiyyatun Nufus (Mimbar Agama Budaya, 2022)
This article examines a community service program aimed at fostering the mental and spiritual development of Muslim children living in the peripheral area of Bogor. The program was initiated in response to limited educational access, inadequate learning facilities, and the insufficient training and welfare of teachers in the area. This study employed a descriptive qualitative approach and was conducted at PAUD Nibrosu Lamhariyah (NILAM), located in Cibeuteung Muara Village, Ciseeng District, Bogor Regency. The program was carried out over a four-month period, involving four teachers and forty-two students divided into two age groups. The learning activities focused on religious education through the Tilawati method for Qur’anic reading and the talaqqi method for tahfidz or memorization. The findings indicate that the program contributed positively to the children’s religious learning outcomes. Around 90% of the students were able to follow the lessons and read qira’ati properly, while 85% were able to memorize up to four short surahs, short hadiths, and ablution prayers along with their practice. These results suggest that structured religious guidance can effectively support the spiritual development of early childhood learners in marginalized communities. However, the implementation of the program still faced several challenges, including limited infrastructure, insufficient financial support, and inadequate attention to teacher welfare in peripheral educational settings.